WEB-BASED INTERACTIVE STRATEGIES FOR EFFECTIVE TOEFL ITP READING SKILLS - Adianto, Arda; Sulistiana, Eva; Nadzifah, Wardatun (Universitas Islam Sumatera Utara (UISU), 2025)
The TOEFL ITP reading comprehension section poses a significant challenge for many EFL learners, necessitating innovative instructional approaches. This study aims to develop and evaluate a dedicated web-based learning platform integrating interactive strategies to enhance reading skills for the TOEFL ITP. Employing a Research and Development (RD) design with the 4D model (Define, Design, Develop, Disseminate), the study involved 109 university students selected through purposive sampling. The platform's development included validation by English teaching and educational technology experts, followed by a limited field test. Data were collected through pre-test/post-test assessments and a usability questionnaire. The results indicated a substantial improvement in reading proficiency, with mean scores increasing from 355.88 to 423.45, a statistically significant gain of 18.98% (Z = -9.019, p .001). Furthermore, user evaluations revealed positive feedback on the platform's accessibility, interactivity, and ability to maintain engagement. This study concludes that the purpose-built web-based platform serves as an effective intervention for improving TOEFL ITP reading skills. It contributes to the field of digital-based EFL instruction by demonstrating the efficacy of a tailored, interactive learning tool for standardized test preparation.